Pengaruh Pelarut dan Temperatur terhadap Tranport Europium (III) melalui Membran Cair Berpendukung - Buchari Buchari; Eti Testiati; Aminudin Sulaeman (Institut Teknologi Bandung, 2003)
Study of the influence of solvents and temperature on the transport of Eu(III) through supported liquide membrane (SLM) has been undertaken. The first step of this work was to determine the best conditions for the extraction. Polytetrafluoroethylene (PTFE) membrane has been used in this research. The thickness of the film is 47 Î¼m and the average pore size is 0.45 Î¼m.The membrane was impregnated in the carrier solutions for 2 hours. The carrier used were di 2-ethylhexyl phosphoric acid (D2EHPA) and tributylphosphate (TBP). Feed compartment contained 100 ppm Eu(III) in a buffer solution. Receiver compartment contained 0.1 M nitric acid. The optimum result has been achieved at feed pH of 3 and a mixture of 0.8 M D2EHPA and 0.2 M TBP in kerosene. At this conditions, 71.74 % of Eu( III) was transported through SLM. The transport percentase ncreased in the solvent order of kerosene>toluena>chloroform>n-hexane>1,2-dichloroethane. The mixture of 75% of kerosene and 25% of chloroform increased the Eu(III)âs transport from 71.74 % to 79.1% compared with the kerosen as a solvent. The elevation of temperature from 25oC to 60oC increased the transport of Eu(III) from 71.74 to 92.26 %. The profile of membrane surface was characterized by scanning electron microscope (SEM).